Association Between the Femoral Stem Design Type and the Risk of Aseptic Revision After Hemiarthroplasty. Issue 5 (1st March 2022) - Okike, Kanu; Chan, Priscilla H.; Reddy, Nithin C.; Burri, Robert A.; Paxton, Elizabeth W.; Prentice, Heather A.
Abstract : Introduction: Although noncemented hemiarthroplasty has been associated with a higher risk of revision surgery as compared with cemented fixation, it remains uncertain whether this increased risk applies to all noncemented stem design types or only a subset. The purpose of this study was to assess the risk of aseptic revision associated with three common types of noncemented stem designs as compared with cemented fixation in the hemiarthroplasty treatment of femoral neck fractures in the elderly patients. Methods: This was a retrospective cohort study of patients aged 60 years and older who sustained a hip fracture and underwent hemiarthroplasty between 2009 and 2018 at one of 35 hospitals owned by a large US health maintenance organization. Hemiarthroplasty fixation was categorized as cemented or noncemented, with the noncemented stems further classified as single wedge without collar, fit and fill without collar, or fit and fill with collar. The primary outcome was aseptic revision, and the median follow-up time was 4.8 years. Results: Of 12, 071 patients who underwent hemiarthroplasty during the study period (average age 82.0 ± 8.4 years, 67.9% women), 807 (6.7%) received a single-wedge stem without collar, 2, 124 (17.6%) received a fit-and-fill stem without collar, 2, 453 (20.3%) received a fit-and-fill stem with collar, and 6, 687 (55.4%) received a cemented stem. Compared with cemented fixation, all the noncemented stem design types were associated with a markedly higher risk of aseptic revision in the multivariable analysis, including single wedge without collar (hazard ratio [HR] 2.00, 95% confidence interval [CI], 1.38 to 2.89, P < 0.001), fit and fill without collar (HR 1.52, 95% CI, 1.14 to 2.04, P = 0.005), and fit and fill with collar (HR 2.11, 95% CI, 1.63 to 2.72, P < 0.001). Conclusion: In the hemiarthroplasty treatment of elderly patients with hip fracture, all routinely used noncemented stem design types were associated with a higher risk of aseptic revision as compared with cemented fixation.